Efficacy and safety of sintilimab plus XELOX as a neoadjuvant regimen in patients with locally advanced gastric cancer: A single-arm, open-label, phase II trial - Guo, Honghai; Ding, Ping’an; Sun, Chenyu; Yang, Peigang; Tian, Yuan; Liu, Yang; Lowe, Scott; Bentley, Rachel; Li, Yaru; Zhang, Zhidong; Wang, Dong; Li, Yong; et al. (Frontiers in Oncology, 2022)
Background: Neoadjuvant chemotherapies have been widely recommended in patients with locally advanced gastric cancer (LAGC). However, the evidence of combining neoadjuvant chemotherapy with anti-programmed death 1 (anti-PD-1) antibody therapy for patients with LAGC is lacking. Thus, we conducted a single-arm phase II trial to evaluate the efficacy and safety of the anti-PD-1 antibody sintilimab plus XELOX regimen (capecitabine plus oxaliplatin) in patients with LAGC. Methods: Patients with LAGC (cT3-4 N+ M0, CY0, P0) were enrolled and received four preoperative cycles of sintilimab (200mg, IV, Q21d) plus XELOX (oxaliplatin 130mg/m2, IV, d1 with capecitabine 1000mg/m2, bid, d1-d14, Q21d) therapy. The primary endpoint was the pathological complete response (pCR) rate. This clinical trial was registered at Chictr.org.cn (Trial number: ChiCTR2000030414). Results: Thirty patients were enrolled from March 2020 to July 2021, with a median age of 62 years (range30-72) and 18(60.0%) males. There were 19(63.3%) patients with PD-L1 CPS≥1.The pCR rate was 33.3% (95% confidence interval (CI), 17.3%-52.8%) and the major pathologic response (MPR) rate was 63.3% (95% CI, 43.9%-80.1%). All the patients underwent R0 resection. The objective response rate (ORR) and the disease control rate (DCR) were 70.0% (95% CI, 50.6%-85.3%) and 100% (95% CI, 88.4%-100%), respectively. Downstaging of the overall TNM stage was observed in 22 (73.3%) patients. The pCR rate in patients with PD-L1 CPS ≥1 and patients with PD-L1 CPS＜1 was 42.1% vs 18.2% (P=0.246), while the MPR rate was 78.9% vs 36.4%(P=0.047). The potential immune-related adverse events (irAEs) were hypothyroidism (3.3%), pneumonia (10.0%), and dermatitis (6.7%). Grade3 common treatment-related adverse events (TRAEs) were ALT increase (3.3%), AST increase (3.3%) and dermatitis (3.3%) during the neoadjuvant therapy. There were no severe complications or death related to the surgery. Conclusion: Sintilimab plus XELOX as neoadjuvant therapy showed an encouraging pCR rate, MPR rate and manageable safety. This combination of regimens might provide a new option for patients with LAGC.